2021
DOI: 10.1212/wnl.0000000000012063
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Neuroimaging Outcomes of Direct Thrombectomy vs Bridging Therapy in Large Vessel Occlusion

Abstract: Objective:To evaluate the comparative safety and efficacy of direct endovascular thrombectomy(dEVT) compared to bridging therapy(BT:IV-tPA+EVT) and assess if BT potential benefit relates to stroke severity, size and initial presentation to EVT vs. non-EVT center.Methods:In a prospective multicenter cohort-study of imaging selection for endovascular thrombectomy[SELECT], anterior-circulation large vessel occlusion (LVO) patients presenting to EVT-capable centers within 4.5hours from last-known-well were stratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
(105 reference statements)
0
20
0
Order By: Relevance
“…The investigators documented an overall shift toward better functional outcomes with bridging therapy compared with direct MT (adjusted cOR 4.51, 95% CI 1.44 to 14.15). The rates of 90-day good functional outcome were numerically but non-significantly higher in the bridging therapy group (47% vs 29%, p=0.14); similarly, the rates of 90-day mortality were numerically but non-significantly lower in the bridging therapy group (13% vs 29%, p=0.10), while the two groups had similar sICH rates 49. These findings were reproduced by a single-center German study that reported higher rates of excellent functional outcome (mRS scores 0–1 or return to prestroke mRS-score) in ‘drip and ship' patients receiving bridging therapy (23% vs 14% for direct MT) 46.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…The investigators documented an overall shift toward better functional outcomes with bridging therapy compared with direct MT (adjusted cOR 4.51, 95% CI 1.44 to 14.15). The rates of 90-day good functional outcome were numerically but non-significantly higher in the bridging therapy group (47% vs 29%, p=0.14); similarly, the rates of 90-day mortality were numerically but non-significantly lower in the bridging therapy group (13% vs 29%, p=0.10), while the two groups had similar sICH rates 49. These findings were reproduced by a single-center German study that reported higher rates of excellent functional outcome (mRS scores 0–1 or return to prestroke mRS-score) in ‘drip and ship' patients receiving bridging therapy (23% vs 14% for direct MT) 46.…”
Section: Resultsmentioning
confidence: 84%
“…A subgroup analysis of the SELECT (Optimizing Patient Selection for Endovascular Treatment in Acute Ischemic Stroke) study evaluated LVO patients who were ‘dripped’ in primary stroke centers and ‘shipped’ to MT-capable centers. This analysis found that the rates of excellent functional outcome (mRS scores of 0–1) were significantly higher in patients receiving bridging therapy (36%) compared with direct MT (10%) 49. The investigators documented an overall shift toward better functional outcomes with bridging therapy compared with direct MT (adjusted cOR 4.51, 95% CI 1.44 to 14.15).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…4 Consequently, exposure times to intravenous thrombolysis before starting endovascular therapy were rather short. Furthermore, in light of the neutral results of a first randomised clinical trial investigating prehospital triage for patients with suspected LVO to enable direct transfer to an 'endovascular-ready hospital' 5 and conflicting data from observational studies, [6][7][8][9] a controversial debate regarding the optimal stroke service structure continues. 10 The basic rationale of a drip-and-ship stroke service, that is, admission to the nearest primary stroke centre, is to provide intravenous thrombolysis as early as possible.…”
Section: Introductionmentioning
confidence: 99%